Dynamics and energetics of PCBP1 binding to severely oxidized RNA - Gillet, Natacha; Dumont, Elise (Frontiers in Molecular Biosciences, 2022)
Oxidatively generated lesions such as 8-oxo-7, 8-dihydroguanine (8-oxoG) on RNA strands constitute a hallmark marker of the oxidative stress in the cell. Poly-C binding protein 1 (PCBP1) is able to specifically recognize severely damaged RNA strands containing two 8-oxoG lesions separated by five nucleobases, which trigger a signaling pathway leading to cell apoptosis. We apply an in silico protocol based on microsecond timescale all-atom classical molecular dynamics simulations associated with conformational and energy analyses to unveil the specific recognition mechanism at a molecular level. By comparing the RNA and protein behavior for sequences with six different damage profiles, our results highlight an allosteric mechanism, allowing a stronger binding of the oxidized guanine at position 9 only if another 8-oxoG lesion is present at position 15, in full agreement with experiments. We assess the role of lysine K23 and the additional ketone group of the oxidized guanine, thanks to computational site-directed mutagenesis.